Erythrocyte sequestration and anemia in severe falciparum malaria. Analysis of acute changes in venous hematocrit using a simple mathematical model. - Davis, T; Krishna, S; Looareesuwan, S; Supanaranond, W; Pukrittayakamee, S; Attatamsoonthorn, K; White, N (1990)
Microvascular erythrocyte sequestration, the characteristic pathological feature of falciparum malaria, was evaluated using a mathematical model in 46 patients with severe infections. From admission radioisotopic circulating red cell volumes and simultaneous venous hematocrits, the model-derived sequestrum hematocrit (mean [95% confidence limits]: 0.70 [0.43-0.97], n = 29) was twice that of peripheral blood (0.33 [0.30-0.36]). Serial reticulocyte and radiolabeled erythrocyte counts indicated that small numbers of cells enter the circulation during initial therapy. The mean fall in hematocrit over 84 h in 26 nontransfused patients conformed to a three-term equation. A first-order decline (t1/2 2.0 h [0.6-3.4]) suggested an average 7.5% plasma volume expansion through rehydration. A zero-order 6.3% (3.1-9.5) fall (t1/2 25.7 h [21.2-30.2]) occurred contemporaneously with a fall in mean parasitemia from 4.5% (3.6-5.4); from these data the model-derived average sequestered erythrocyte volume (4.8% of the admission hematocrit) was similar to the peripheral parasite burden. A second, first-order fall (t1/2 1,047 h [278-1,816]) indicated loss of uninfected erythrocytes with mean lifespan 62 d. Predicted total plasma volume expansion during initial therapy (21.2%) was similar to radioisotopic estimates in 11 patients (17.3% [2.0-33.1]). Application of the model to individual patient data showed wide variations in relative proportions of circulating and sequestered parasitized cells. The model provides evidence of the nature and fate of all parasitized erythrocytes in malaria.